Effectiveness of a Virtual Reality Forest on People With Dementia: A Mixed Methods Pilot Study. (15th March 2017) - Moyle, Wendy; Jones, Cindy; Dwan, Toni; Petrovich, Tanya
Abstract: Purpose of the Study: To measure and describe the effectiveness of a Virtual Reality Forest (VRF) on engagement, apathy, and mood states of people with dementia, and explore the experiences of staff, people with dementia and their families. Design and Methods: A mixed-methods study conducted between February and May 2016. Ten residents with dementia, 10 family members, and 9 care staff were recruited from 2 residential aged care facilities, operated by one care provider, located in Victoria, Australia. Residents participated in one facilitated VRF session. Residents' mood, apathy, and engagement were measured by the Observed Emotion Rating Scale, Person–Environment Apathy Rating Scale, and Types of Engagement. All participants were interviewed. Results: Overall, the VRF was perceived by residents, family members, and staff to have a positive effect. During the VRF experience, residents experienced more pleasure ( p = .008) and a greater level of alertness ( p < .001). They also experienced a greater level of fear/anxiety during the forest experience than the comparative normative sample ( p = .016). Implications: This initial, small-scale study represents the first to introduce the VRF activity and describe the impact on people with dementia. The VRF was perceived to have a positive effect on people with dementia, although, compared to the normative sample, a greater level of fear/anxiety during the VRF was experienced. This study suggests virtual reality may have the potential to improve quality of life, and the outcomes can be used to inform the development of future Virtual Reality activities for people with dementia.